1998
DOI: 10.1055/s-2007-978852
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Plasma Lipid Levels and Pseudocholinesterase Activity in Hypothyroidism

Abstract: The relation of plasma lipids and pseudocholinesterase (PChE) activity was studied in rats made hypothyroid by treatment with propylthiouracil (0.05% in drinking water for 28 days) and in hypothyroid patients prior and after 1-thyroxinetherapy (1. week 25-50kg, 2.-4. week 100 pg daily). In rats, thyroid hormone deficiency caused a significant increase in plasma and adipose tissue PChE activity as well as total plasma cholesterol (IC) concentration, and a decrease in plasma triglyceride (TG) concentration. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Total cholesterol and lowdensity lipoprotein cholesterol were significantly increased under hypothyroidism conditions in both rat strains; however, highdensity lipoprotein cholesterol was elevated only in the WKY rats. In agreement with previous data, the lowered thyroid hormone levels in rats of both strains decreased triglyceride levels in the blood, which contrasts with the effect observed in humans (Popović et al, 1998). The results obtained in the current research confirmed and extended the data showing the presence of hypothalamicpituitary-thyroid (HPT) axis disturbance in WKY rats and indicated the possible causes of the weaker action of these hormones in the brain compared to their action in peripheral tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Total cholesterol and lowdensity lipoprotein cholesterol were significantly increased under hypothyroidism conditions in both rat strains; however, highdensity lipoprotein cholesterol was elevated only in the WKY rats. In agreement with previous data, the lowered thyroid hormone levels in rats of both strains decreased triglyceride levels in the blood, which contrasts with the effect observed in humans (Popović et al, 1998). The results obtained in the current research confirmed and extended the data showing the presence of hypothalamicpituitary-thyroid (HPT) axis disturbance in WKY rats and indicated the possible causes of the weaker action of these hormones in the brain compared to their action in peripheral tissue.…”
Section: Discussionsupporting
confidence: 91%
“…However, our current results showed that two hypothyroidism groups elicited significantly reduced plasma TG (Fig. 3A), which may be partly explained by both significantly increased serum pseudocholinesterase (PChE) and lipoprotein lipase (LPL) activity elicited by TH deficiency in animals, although the activities of both enzymes are reduced in hypothyroid patients [32]. Moreover, APOC3, an inhibitor of LPL activity, plays a crucial role in the catabolism of triglycerides, and the suppressed expression of the gene may be connected with the raised LPL activity and then the decrease in plasma TG level [33], which is consistent with our current result (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Whereas LPL activity positively correlates with TH levels in humans (9,11), hypothyroidism in rats increases both adipose and heart LPL mass and activity via a translational mechanism involving its 3Ј-untranslated region (57), whereas T 3 reverses these effects (58). Accordingly, PTU-induced hypothyroidism in rats has been associated with reductions in plasma TG (49,50,59,60). Nevertheless, despite these overall effects, a number of indirect observations suggest the existence of an underlying hypotriglyceridemic response to T 3 in rodents.…”
Section: Discussionmentioning
confidence: 99%